The Impact of Autocratic Leadership Style and Work Motivation towards Employee Performance on Retail Company in Sidoarjo Indonesia - Mahida Eka Mahdayanthi; Mudji Astuti (Indonesian Journal of Law and Economics Review, 2020)
This study aims to determine autocratic leadership style, communication and work motivation Against Employee performance at PT. Candi Jaya Amerta. This research includes the type of quantitative research with hypothesis testing. The sample used in this study were 72 employees at PT. Candi Jaya Amerta. The analytical tool used in this research is multiple linear regression analysis, determinant coefficient (R2), multiple correlation coefficient (R), f test, t test, and classic assumption test using SPSS version 18 for windows. Primary data in this study were obtained from questionnaires whose measurement used a Likert scale that was tested for validity and reliability. The results of this study prove that Autocratic Leadership Style, Communication and Work Motivation Against Employee Performance simultaneously affect employee Performance. communication partially affects employee performance, work motivation partially influences employee performance, job satisfaction also partially affects employee Performance.